The Influence of Job Training, Motivation, and Work Environment on Employee Performance at PT. Telekomunikasi Indonesia, Tbk Kediri City - Asiska, Yuke Sepvi Dinata; Kristanti, Desi; Yunanto, Yogi; Bagaskara, Whicka Galuh (Airlangga Journal of Innovation Management, 2024)
This investigation intends to determine and anatomize the effect of job training, motivation, and work environment on employee performance at PT Telekomunikasi Indonesia, Tbk Kediri City. A key element in a company's success is employee performance. Job training, motivation, and a positive work environment are necessary for effective employee performance. Data gathering techniques include distributing questionnaires and performing direct talks with 50 permanent employees of PT. Telekomunikasi Indonesia, Tbk Kediri City. Analyzing data found that job training, motivation, and work environment affect employee performance at PT. Telekomunikasi Indonesia, Tbk Kediri City. This study has a noteworthy impact on job training, motivation, and work environment on employee performance. This research contributes science to human resources.  The results can be applied to PT. Telekomunikasi Indonesia, Tbk Kediri City, to optimize job training, motivate employees, and improve a good work environment, so that it can affect employee performance and achieve company success. In further research, it’s hoped that they will research broader and different research objects. Thus, the results attained will benefit numerous parties.